Characteristics of the Wind Environment above Bridge Deck near the Pylon Zone and Wind Barrier Arrangement Criteria - Dalei Wang; Yiquan Zhang; Mengjin Sun; Airong Chen (Applied Sciences, 2020)
Due to the complex arrangement of structural components in the vicinity of bridge pylon zones, the wind environment above bridge decks is very complicated. A sudden change in wind speed exerts an adverse effect on vehicle control stability. In order to investigate the characteristics of the flow field in the vicinity of the bridge pylon, the wind environment near an inverted Y-shaped pylon is studied by experimental and numerical methods. From the flow visualization and the wind speed measurement in the wind tunnel and the numerical simulation created using Fluent software, specific patterns of the direction and magnitude of wind speed at a range of vehicle height above the bridge deck near the pylon zone were observed along the longitudinal direction. This distribution pattern of the wind environment can effectively guide the wind barrier arrangement near the bridge pylon zone. Combined with the two safety evaluation indicators proposed in this paper, the optimal arrangement scheme of wind barriers in the bridge pylon zone of Sutong Bridge is determined. This paper deepens the understanding of the wind environment near the pylon zone and proposes an evaluation method for the wind environment near the pylon zone, which can serve as the basis for wind barrier arrangement in similar research projects.